THE STUDY OF ZOOMORPHIC METAPHORS IN SCIENTIFIC SOURCES (Eureka Journal of Language, Culture & Social Change, 2026)
Zoomorphic imagery has remained an integral component of literary expression from the culture of antiquity to the present day. Throughout different stages of human history, people's understanding and interpretation of the world were significantly influenced by their interactions with animals. By observing animals’ behavior, habits, physical appearance, and ways of life, humans gradually developed specific perceptions of various animal species as carriers of particular symbolic meanings and cultural representations. As human cognition evolved, these perceptions and attitudes toward animals underwent continuous transformation, giving rise to diverse cultural interpretations and symbolic associations. Over time, the emergence and further development of zoomorphic representations have led to the formulation of various theories concerning their origins, evolution, and perception in human consciousness across different historical periods. This article examines primitive conceptions of animals, the earliest manifestations of zoomorphism, and its various forms. It also explores the extent to which these representations were reflected in subsequent stages of cultural and linguistic development and how they were preserved in later periods of antiquity. Particular attention is paid to the historical continuity and cultural significance of zoomorphic imagery as a means of conceptualizing human experience and understanding the surrounding world.
Keywords: zoomorphic metaphor, metaphorical units, zoomorphic imagery, animal representation, metaphorical conceptualization, anthropocentrism, comparative analysis.